Three-dimensional modeling of the reactive transport of CO2 and its impact on geomechanical properties of reservoir rocks and seals. (March 2016) - Nguyen, Ba Nghiep; Hou, Zhangshuan; Bacon, Diana H.; Murray, Christopher J.; White, Mark D.
Highlights: We develop a coupled hydro-geochemical-mechanical approach to analyze CO2 reservoirs. We model the reactive transport of CO2 causing changes in mineralogy. Rocks' elastic properties are computed using an Eshelby–Mori-Tanaka model. We determine the impact of reactive transport of CO2 on geomechanical properties. Reduction in elastic modulus about 5% is found for the injection location after 20 years. Abstract: This article develops a model to analyze CO2 reservoirs using the STOMP-CO2 -R code that is interfaced with the ABAQUS ® finite element package. The STOMP-CO2 -R/ABAQUS ® simulator accounts for the reactive transport of CO2 causing changes in mineralogy that modify the geomechanical properties of reservoir rocks and seals. Rocks' elastic properties that vary during CO2 injection and govern the poroelastic behavior of rocks are modeled by an Eshelby–Mori-Tanka approach. A three-dimensional (3D) STOMP-CO2 -R model for a CO2 reservoir containing a vertical fault was built to analyze a formation containing a reaction network with 5 minerals: albite, anorthite, calcite, kaolinite and quartz. A 3D ABAQUS ® model that maps this STOMP-CO2 -R model was built for the analysis using STOMP-CO2 -R/ABAQUS ® . The results show that after a long period of CO2 injection the mineralogical changes significantly reduced the permeability and elastic modulus of the reservoir in front of the fault leading to a reduction of the pressure margin to fracture at and beyond the injection location. The impact of reactive transport of CO2 on the geomechanical properties of reservoir rocks and seals are studied in terms of mineral composition changes that affect the rock stiffness, stress and strain distributions, and pressure margin to fracture.